Public school teachers' occupational stress across different school types: a nationwide survey during the prolonged COVID-19 pandemic in Japan - Kenjiro Tsubono; Sachiko Mitoku (Frontiers Media S.A., 2023)
ObjectivesSchool teaching is regarded as one of the most stressful professions worldwide. To maintain schoolteachers' mental health, the factors influencing occupational stress among schoolteachers must be clarified. This study aimed to investigate public school teachers' work-related stress considering the differences in school types using data from a large-scale nationwide survey conducted during the prolonged coronavirus disease 2019 (COVID-19) pandemic in Japan.MethodsData from a nationwide survey of public school teachers performed between June 2019 and December 2022 were analyzed. The dataset consisted of repeated cross-sectional data. The total number of participants was 270,777 in 2019, 296,599 in 2020, 299,237 in 2021, and 307,866 in 2022. Information on working hours, job demands, workplace support, stress response, and perceived main stressors were assessed for each type of public school.ResultsRegardless of school type, quantitative workload and long working hours were the most significant factors affecting teachers' stress responses. However, stress-related factors among teachers varied significantly between school types. The percentage of junior high school teachers who perceived "extra-curricular club activities" as their main stressor was the highest among all school types. The highest proportion of elementary school teachers perceived "dealing with difficult students" as their main stressor. Meanwhile, interpersonal conflict scores were the highest among special needs school teachers. Teachers' workload and stress levels significantly increased in the third year of the COVID-19 pandemic (2022) compared to the pre-pandemic year (2019) in all school types despite the marginally small score differences.ConclusionsThis study highlighted the importance of reducing teachers' workload for their mental health regardless of school types. Meanwhile, perceived work-related stress among teachers differed significantly between school types. Given the possible prolonged impacts of the pandemic on teachers' occupational stress, teachers' stress levels must be monitored throughout and after the pandemic. The results suggest that increasing the number of schoolteachers and support staff and providing adequate organizational support are necessary to prevent teachers' sick leave due to mental disorders. In addition, taking comprehensive countermeasures against teachers' occupational stress, considering the differences in school types, is crucial for safeguarding schoolteachers' mental health.